PERANCANGAN PROTOTIPE ROBOT PENGHALANG GARIS BERBASIS ROBO TX CONTROLLER - Subiyantoro Subiyantoro; Nurwijayanti KN (JURNAL TEKNOLOGI INDUSTRI, 2012)
Robot  barrier  line designed  and  developed  as  a  platform   for the development  of  robots in the  future. Robot  control system  was  designed  based  on  Robo TX Controller  and  is  designed  to be able to move forward, backward, and turn in place or the desiredlocation. In  the  design  o  f the  prototype   robot  is  necessary a barrier line controller ( ROBO TX Controller ) and    infrared   trail  sensor, where  the   sensor  can  distinguish  between  black  and  white. If  the  robot  track  a black  line  then  the  robot  will  stop  and    make  a   turn   to   continue  it  is  work. Obtained   in  the  testing  and   analysis    that   the  robot   is   able  to   do  it  is   job  as  it   should   be .   Data  tables   from  the  test  range   for   robot obtained error of  0.80   %  to  0.86  %  in  the  black  line  sensor readings. Key words : Robo TX, Sensor, Prototype, Autonomous